Neuropeptide Y neurons in the basolateral amygdala project to the nucleus accumbens and stimulate high-fat intake - Yamada, Shunji; Kojima, Kazunori; Tanaka, Masaki (Frontiers in Cellular Neuroscience, 2025)
Neuropeptide Y (NPY) is a 36-amino acid neuropeptide that is widely expressed in the central nervous system, including in the nucleus accumbens (NAc), hypothalamus, and amygdala. The NAc involved in several behaviors, including reward, motivation processes, and feeding behavior. Here, we demonstrate in male mice that NPY input from the basolateral amygdala (BLA) to the NAc is involved in the preferential consumption of a high-fat diet (HFD). First, we demonstrated the NPY input to the NAc from the BLA by injecting adeno-associated virus (AAV)(retro)-FLEX-mCherry into the NAc of NPY-Cre mice. We also confirmed that BLA NPY neurons project exclusively to the NAc by injecting AAV(dj)-hSyn-FLEx -mGFP-2A-Synaptophysin-mRuby into the BLA. Usually, a HFD drives enhanced food intake than a standard chow diet after repetitive exposure. The optogenetic inactivation of BLA NPY neurons projecting to the NAc caused a significant decrease in HFD intake for a 1-h period, while optogenetic activation of these neurons induced the opposite effect. Furthermore, bilateral injection of an NPY receptor type 1 (Y1R) antagonist into the NAc significantly decreased HFD intake for 1-h period compared with vehicle injection, while, conversely, injection of a Y1R agonist enhanced HFD intake. These results suggest that BLA NPY neurons projecting to the NAc mediate preferential HFD intake via NAc-localized Y1R.